Towards Inclusive Innovation: The Role of Open Science - Mboa Nkoudou, Thomas Hervé (My University, 2020)
Workshop on Science, Technology and Innovation for the SDGs Meeting of the IATT and 10-Member group under the TFM in preparation of the Multi-Stakeholder Meeting on Science, Technology and Innovation for the SDGs 2020 Room C1, Vienna International Centre, Vienna, Austria, 3 – 5 February 2020 Co-organized by DESA, UNCTAD, UNOSD, OOSA, and UNIDO.
Keywords: Open Science; Africa; Innovation